LAW IN THE AGE OF ARTIFICIAL INTELLIGENCE - Abdujalilov Shaxriyor; Aliyev Mirzohid (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article comprehensively examines the new legal relations, risks and opportunities arising as a result of the rapid development of artificial intelligence technologies. The study analyzes the legal status of artificial intelligence systems, issues of liability arising from their activities, requirements for the protection of personal data and problems of algorithmic justice on a scientific basis. It also examines the comparative legal aspects of current regulatory documents, international standards and approaches to regulating the field of artificial intelligence in different countries. The article provides proposals and recommendations on the integration of artificial intelligence into the legal system, ensuring human rights and creating a safe innovative environment. The study substantiates the need to improve legal mechanisms in the era of artificial intelligence and provides relevant scientific conclusions for future legal policy.